Pelatihan dan Pendampingan Kebugaran dan Kesehatan untuk Anak Penyandang Disabilitas di SKh 01, Kabupaten Lebak - Dena Widyawan; Mochamad Derry Prasaja; Rizki khoirul Yakin; Sul Abidin; Weny Widyawati Bastaman (UNIVERSITAS NGUDI WALUYO, 2026)
Low physical activity participation and the lack of structured fitness programs in special schools (SKh) lead to a high risk of secondary health problems among children with disabilities. This community service activity aimed to improve physical fitness and health knowledge of children, as well as to equip teachers and parents with adaptive exercise facilitation skills at SKh 01 Lebak Regency, Banten. The method used a participatory approach with four stages: preparation, training, implementation mentoring, and evaluation. The intervention included adaptive gymnastics, circuit games, game-based nutrition and personal hygiene education, and the development of a daily exercise program. Results showed significant improvements in flexibility, muscle strength, cardiorespiratory endurance (p<0.001), and health knowledge scores (from 51.2 to 79.8; p<0.001). Teachers' and parents' capacity to guide adaptive physical activity increased, and the school has integrated the program into its regular schedule. This model has proven effective and has the potential to be replicated in other special schools. ABSTRAK Rendahnya partisipasi aktivitas fisik dan minimnya program kebugaran terstruktur di sekolah khusus (SKh) menimbulkan risiko kesehatan sekunder yang tinggi pada anak penyandang disabilitas (tunagrahita ringan, tunadaksa ringan, tunarungu, tuna netra). Kegiatan pengabdian ini bertujuan untuk meningkatkan kebugaran jasmani dan pengetahuan kesehatan anak, serta membekali guru dan orang tua dengan keterampilan pendampingan latihan adaptif di SKh 01 Kabupaten Lebak, Banten. Metode pelaksanaan menggunakan pendekatan partisipatif dengan empat tahapan, yaitu persiapan, pelatihan, pendampingan implementasi, dan evaluasi. Intervensi meliputi senam adaptif, permainan sirkuit, edukasi gizi dan kebersihan diri berbasis permainan, serta penyusunan program latihan harian. Hasil menunjukkan peningkatan signifikan pada fleksibilitas, kekuatan otot, daya tahan kardiorespirasi (p<0.001), serta skor pengetahuan kesehatan (dari 51.2 menjadi 79.8; p<0.001). Kapasitas guru dan orang tua dalam memandu aktivitas fisik adaptif meningkat dan sekolah telah mengintegrasikan program ke dalam jadwal rutin. Model ini terbukti efektif dan berpotensi direplikasi di SKh lain.